1973
DOI: 10.3758/bf03212383
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the tactual field of view

Abstract: Can tactual information be acquired simultaneously by several different fingers? Blind and sighted Ss were asked to scan vertical displays of braille (consisting of either one or two dots) with the index and middle fingers on each hand-using one, two, or four fingers at the same time. Stimuli were recognized most rapidly when the displays were scanned by two fingers on different hands and least rapidly when two fingers on the same hand were used; performance was similar with one finger and with four fingers. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
6
27
0
Order By: Relevance
“…The present experiments suggest that one reason for Lappin and Foulke's (1973) observation that braille cell perception was better with two fingers on opposite hands is that it is easier to attend to two fingers bilaterally situated. In this regard, it is noteworthy that Tadoma users typically use a single hand (Reed et al, 1982).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The present experiments suggest that one reason for Lappin and Foulke's (1973) observation that braille cell perception was better with two fingers on opposite hands is that it is easier to attend to two fingers bilaterally situated. In this regard, it is noteworthy that Tadoma users typically use a single hand (Reed et al, 1982).…”
Section: Discussionmentioning
confidence: 45%
“…One behavioral measure that suggests that improvement might be seen using fingers from two hands comes from a study of braille reading by Lappin and Foulke (1973). In their study, subjects identified braille cells with one finger, two fingers, or four fingers.…”
mentioning
confidence: 99%
“…Importantly, although some of the published psychophysical findings indicate that concurrent input from mirrorsymmetric sites on the two hands can enhance tactile perceptual performance above that obtained with unilateral stimulation, other studies indicate that tactile input from the two hands can lead to perceptual performance inferior to that observed when the stimulus is applied unilaterally. As examples of the former, (1) Lappin and Foulke (1973) observed that, when a subject scans the pattern using two fingers on opposite hands, Braille cell perception improves over that achieved unilaterally, (2) Craig (1985) reported that a subject's ability to correctly identify a split tactile pattern (dot array) is substantially greater when the two halves of the pattern are presented simultaneously to two fingers on opposite hands (relative to the performance achieved when the two halves are delivered to two fingers, neighboring or nonneighboring, on the same hand), and (3) Essick and Whitsel found that human subjects' accuracy of perceived direction of tactile motion on the hands improves greatly over that obtained with unilateral stimulation when the bilateral stimuli (the sites on the two hands were mirror symmetric) move across the two sites at the same time, in the same direction, and at the same velocity. Essick and Whitsel also reported that, whenever the physical properties of the brushing stimulus applied to one hand differed in some way (e.g., in direction, velocity, relative timing) from those of the stimulus to the opposite hand, the subject's ability to accurately report direction of bilaterally applied stimulus motion declined, often reaching performance levels well below those achieved when each moving stimulus was applied unilaterally (Essick and Whitsel, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Blind adults are better than blindfolded sighted people at using the two hands in parallel to recognize shape and orientation (see, e.g., Foulke & Warm, 1967;Warm & Foulke, 1968). Experienced subjects are likely to use the two forefingers in paral1elto scan the sides ofa shape (see, e.g., Lappin & Foulke, 1973) for explicit judgments of symmetry.…”
Section: Discussionmentioning
confidence: 99%